Explaining the Factors Affecting the Competence Development of Managers in Public Hospitals with an Approach Based on the General Policies of the Health System - Saied Moradi; Mohammadreza Rabiee Mandejin; Mohammad Mohammadi (بیمارستان)
Background and purpose: The implementation of key components in the selection of meritorious candidates, ensuring they possess the necessary capabilities for key and sensitive positions, and adhering to the principle of meritocracy in the distribution of power and division of duties and responsibilities among society’s elites, not only contributes to the stability, growth, and development of the country but is also one of the secrets to the success and longevity of leaders. Therefore, this article aims to explain the factors influencing the competence development of public hospital managers, guided by the general policies of the health system. Methods: The research was developmental in purpose and qualitative in method, utilizing thematic analysis. The statistical population included books, articles, documents, and knowledgeable human resources, comprising government management experts, hospital managers with a master's degree or higher, and at least ten years of experience in hospital management. The study employed a purposive approach with semi-structured interviews, continuing until theoretical saturation was reached (16 interviews) Results: A total of 18 competence development factors were identified, categorized into 75 components and 671 dimensions. The implementation of the Strauss-Corbin model revealed that causal conditions included leadership, doctors, and staff. Intervening conditions encompassed the economy, research technology, and education. In addition to goals and missions, organizational platform, creativity, services, and structure were considered contextual conditions. Human resource management, public relations, and religion were identified as strategies, while the resulting consequences were classified into expertise, a knowledge-based economy, and internationalization. Conclusion: According to the research findings, it appears that to advance, upgrade, and excel in hospitals that play a critical role in the health of society, these identified factors can be utilized to enhance the competence of public hospital managers.